New Classification of the Infiltration Degree of Submucosal-Invaded Carcinomas, and its Clinical Usefulness - Otani, Y.; Kobayashi, K.; Yokoyama, K.; Mitomi, H.; Saigenji, K.; Katsumata, T.; Sada, M.; Igarashi, M. (Nippon Daicho Komonbyo Gakkai Zasshi, 2001)
We classified sm carcinoma based on the distance of infiltration in the vertical direction in the submucosal layer, and also investigated its clinical significance. [Subjects and Methods] We examined 250 sm carcinoma lesions. Lesions with a vertical infiltration distance of less than 1000μm were classified as sm-slight carcinoma (sm-S carcinoma), and lesions with a vertical infiltration distance of greater than 1000μm, or lesions with infiltration to the deep submucosal layer, in which identification of the muscularis mucosae was difficult, were classified as sm-massive carcinoma (sm-M carcinoma). Then, we investigated the correlation between the infiltration degree of sm carcinoma and the frequencies of lymph vascular infiltration, lymph node metastasis, and recurrence after endoscopic or surgical resection of the tumor. We also investigated the ability of EUS to diagnose the depth of cancerous invasion, in 85 lesions. [Results] 1) The lymph vascular infiltration rate was only 10% in sm-S carcinomas (62 lesions), and metastasis was not observed. But in sm-M carcinomas (188 lesions), the lymph vascular infiltration rate was 59%, and lymph node metastasis and recurrence after resection were also observed in 13% and 4% of the lesions, respectively. 2) Differentiation between mucosal or sm-S carcinomas, which were generally treated endoscopically, and sm-M carcinomas, which were suitable for surgical operation, was possible in 88% of sm carcinomas by EUS. [Conclusion] It is appropriate to subclassify sm carcinoma based on vertical infiltration distance. Sm-S carcinoma is believed to be an indication for endoscopic resection, in a strict sense. And, EUS is useful in planning treatment for sm carcinoma.